Fiber Surface Modification Technology for Fiber-Optic Localized Surface Plasmon Resonance Biosensors - Zhang, Qiang (Molecular Diversity Preservation International (MDPI), 2012)
Considerable studies have been performed on the development of optical fiber sensors modified by gold nanoparticles based on the localized surface plasmon resonance (LSPR) technique. The current paper presents a new approach in fiber surface modification technology for biosensors. Star-shaped gold nanoparticles obtained through the seed-mediated solution growth method were found to self-assemble on the surface of tapered optical fibers via amino- and mercapto-silane coupling agents. Transmitted power spectra of 3-aminopropyltrimethoxy silane (APTMS)-modified fiber were obtained, which can verify that the silane coupling agent surface modification method is successful. Transmission spectra are characterized in different concentrations of ethanol and gentian violet solutions to validate the sensitivity of the modified fiber. Assembly using star-shaped gold nanoparticles and amino/mercapto silane coupling agent are analyzed and compared. The transmission spectra of the gold nanoparticles show that the nanoparticles are sensitive to the dielectric properties of the surrounding medium. After the fibers are treated in t-dodecylmercaptan to obtain their transmission spectra, APTMS-modified fiber becomes less sensitive to different media, except that modified by 3-mercaptopropyltrimethoxy silane (MPTMS). Experimental results of the transmission spectra show that the surface modified by the gold nanoparticles using MPTMS is firmer compared to that obtained using APTMS.